Having regard for stakeholders in practising enlightened shareholder value. (2nd January 2019) - Keay, Andrew
ABSTRACT: Section 172(1) of the Companies Act 2006 introduced the principle of enlightened shareholder value (ESV) to UK law. The provision imposes a duty on directors to act in good faith, in a manner that they consider will promote the success of the company for the benefit of shareholders. The subsection also requires directors to have regard to certain factors when doing this. This is the enlightened aspect of ESV, as these factors encompass interests of different stakeholders, such as employees and customers. Uncertainty prevails over several elements of s 172(1), and this paper addresses this uncertainty over the directors' obligation to have regard to these factors. It examines the factors in the provision and what it means for directors to have regard to them. It also explores what directors are to do when their actions will lead to a conflict between different factors.